Narwhal and Jelly: Narwhal's School of Awesomeness - Book 6 - Clanton, Ben, 1988- (Toronto : Tundra Books, 2021)
"Narwhal and Jelly become the coolest teachers in the world wide waters in the hilarious sixth book of this blockbuster graphic novel series! Dive into four new stories about Narwhal and Jelly becoming substitute teachers! The two best friends come across an enthusiastic school of fish one morning. Unfortunately, Mr. Blowfish, their teacher, has come down with a cold, and class will have to be cancelled . . . until Professor Knowell (Narwhal) and Super Teacher (Jelly) volunteer to help out! The first subject is Wafflematics, in which Narwhal and Jelly calculate the number of waffles needed to feed the class. That's what we're chalking about! Next up is a super-fun science scavenger hunt, followed by a game of "Tag! You're Awesome!" at recess. Narwhal's teaching methods may be unconventional, but with Jelly's help, the two teach (and learn) with their trademark positivity and humor. Before they know it, the day is over . . . but what grade will Narwhal receive from Jelly?"--
Keywords: Narwhal -- Comic books, strips, etc; Jellyfishes -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc; Ocean -- Comic books, strips, etc; Narwhal -- Fiction; Jellyfishes -- Fiction; Marine animals -- Fiction; Ocean -- Fiction; Cartoons and comics; Comics (Graphic works); Graphic novels